OPTIMIZATION OF REGENERATIVE BRAKING EFFICIENCY IN ELECTRIC VEHICLES: ADVANCED CONTROL STRATEGIES AND NOVEL DYNAMIC MODELING - Mamadaliev Foziljon Abdullaevich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This  paper presents  an  advanced  analytical  study  on  optimizing  regenerative braking efficiency in modern electric vehicles (EVs). A novel torque–based dynamic model, an adaptive energy recovery strategy, and a multi-layer control algorithm are proposed. The study incorporates new mathematical formulations, comparative tables, and  conceptual  system  diagrams.  Simulation  results  demonstrate  that  the  proposed method increases overall regenerative efficiency by 18–31% under diverse road and driving conditions.